Sulfide solid electrolyte and method for producing same, and solid-state battery

CN123018109APending Publication Date: 2026-10-30SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611405738.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的主要目的在于提供一种硫化物固体电解质及其制备方法、固态电池,以解决现有技术中硫化物固体电解质存在空气稳定性和电化学稳定性较差等问题

Benefits of technology

[0015]应用本发明的技术方案,本申请的硫化物固体电解质通过包覆上述双包覆层,能够提高硫化物固体电解质的离子电导率、空气稳定性和电化学稳定性。具体地,本申请的第一包覆层(碘化锂层)能够与硫化物电解质内核之间形成稳定的化学键合,使其不易在电池循环过程中脱落。第一包覆层中的碘化锂能够主动诱导锂离子的均匀沉积,抑制锂枝晶的生长,从而大大提高硫化物固体电解质的空气稳定性,并且改善硫化物固体电解质对电极界面的稳定性,从而降低界面阻抗。此外,第一包覆层在电池的工作过程中具有主动调控锂离子迁移的能力,从而实现从“被动保护”到“主动界面调控”的技术跃升,不仅能够使硫化物固体电解质保持良好的离子传导性能,还能够在锂金属负极界面处保持良好的电化学稳定性,在电池循环过程中形成稳定的固体电解质界面层,从而提高电池的循环稳定性。第二包覆层(碘单质层)中的碘单质具有疏水性,不仅能够填充第一包覆层表面的微观缺陷,还能够形成致密的物理阻隔层,从而进一步提升硫化物固体电解质的空气稳定性。综上,本申请的硫化物固体电解质具有较高的离子电导率、良好的空气稳定性和电化学稳定性,且包覆层不易脱落,从而提升电池的电化学性能和循环性能以及延长循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a sulfide solid electrolyte, a preparation method thereof and a solid-state battery. The sulfide solid electrolyte comprises a sulfide electrolyte core and a first coating layer and a second coating layer which are sequentially coated on the outer surface of the sulfide electrolyte core from inside to outside; the first coating layer comprises lithium iodide; and the second coating layer comprises iodine. The sulfide solid electrolyte has high ionic conductivity, good air stability and electrochemical stability, and the coating layer is not easy to fall off, so that the electrochemical performance and cycle performance of the battery are improved, and the cycle life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a sulfide solid electrolyte, its preparation method, and a solid-state battery. Background Technology

[0002] Secondary batteries are crucial for energy conversion and storage. Among them, all-solid-state batteries utilize a non-flammable, high-temperature resistant, non-corrosive, and non-volatile solid electrolyte as the lithium-ion transport channel, solving problems such as electrolyte leakage and thermal runaway in traditional lithium-ion batteries and avoiding safety hazards. Furthermore, because no electrolyte is needed and lithium metal can be used as the negative electrode, the battery's weight is effectively reduced. Therefore, solid-state batteries possess extremely high potential energy density. However, current solid-state batteries are mainly limited by the significant challenges in industrializing solid electrolytes, and large-scale mass production remains a long way off.

[0003] Sulfide solid electrolytes not only possess extremely high ionic conductivity, even approaching that of electrolytes, but also have a wide electrochemical window, making them compatible with various electrode material systems and showing great potential for development in all-solid-state batteries. However, sulfide solid electrolytes suffer from poor stability and are highly susceptible to hydrolysis in humid air, leading to a decrease in ionic conductivity and significantly limiting their application and production. Furthermore, severe interfacial side reactions occur when sulfide solid electrolytes come into contact with lithium metal, resulting in increased interfacial impedance and affecting the performance of all-solid-state batteries. To address this issue, most current approaches employ element doping strategies. For example, Chinese patent application CN110085908A proposes a high-air-stability inorganic sulfide solid electrolyte, its preparation method, and its application. This method improves air stability by replacing some or all of the phosphorus (P) element in the sulfide electrolyte with sulfur (Sb). However, this method involves numerous and complex preparation steps. Therefore, there is an urgent need to develop a sulfide solid electrolyte with a simple preparation method, high ionic conductivity, and good air and electrochemical stability. Summary of the Invention

[0004] The main objective of this invention is to provide a sulfide solid electrolyte and its preparation method, as well as a solid-state battery, to solve the problems of poor air stability and electrochemical stability of sulfide solid electrolytes in the prior art.

[0005] To achieve the above objectives, according to one aspect of the present invention, a sulfide solid electrolyte is provided, the sulfide solid electrolyte comprising a sulfide electrolyte core and a first coating layer and a second coating layer sequentially coating the outer surface of the sulfide electrolyte core from the inside out; the first coating layer comprises lithium iodide; the second coating layer comprises elemental iodine.

[0006] Furthermore, the chemical formula of the sulfide electrolyte core is (100-xy)Li₂S·xP₂S₅·yM m N n , 0≤x<100, 0≤y<100, 0≤x+y<100, 0≤m<4, 0≤n<6, M is selected from any one or more of Li, Ge, Si, Sn and Sb, and N is selected from any one or more of Se, S, O, Cl, Br and I.

[0007] Furthermore, the D50 particle size of the sulfide electrolyte core is 2~10 μm; and / or, the mass percentage of the first coating layer in the sulfide solid electrolyte is 0.1~6%; and / or, the mass percentage of the second coating layer in the sulfide solid electrolyte is 0.1~6%.

[0008] Furthermore, the mass ratio of the first coating layer to the second coating layer is (0.2~5):1.

[0009] According to another aspect of the present invention, a method for preparing the above-mentioned sulfide solid electrolyte is provided, the method comprising: step S1, mixing raw materials including a sulfide electrolyte core and an iodine source and performing a first heat treatment, wherein the iodine source forms iodine vapor and deposits on the outer surface of the sulfide electrolyte core, and performing a second heat treatment to generate lithium iodide on the outer surface of the sulfide electrolyte core, forming a first coating layer, thereby obtaining an intermediate product; step S2, performing a third heat treatment on the intermediate product to deposit elemental iodine on the outer surface of the intermediate product, forming a second coating layer, thereby obtaining a sulfide solid electrolyte; wherein the temperature of the second heat treatment is higher than the temperature of the first heat treatment.

[0010] Furthermore, in step S1, the mass ratio of the sulfide electrolyte core to the iodine source is 100:(0.5~10), and the iodine source is elemental iodine.

[0011] Further, in step S1, the mixing time is 0.5~3h, the mixing temperature is 20~30℃, and the mixing atmosphere is argon and / or nitrogen; the mixing method is selected from any one or more of stirring mixing, shearing mixing, ball milling mixing, twin-screw extrusion mixing and grinding mixing.

[0012] Further, in step S1, the temperature of the first heat treatment is 40~100℃ and the time of the first heat treatment is 1~24h; the temperature of the second heat treatment is 150~300℃ and the time of the second heat treatment is 1~8h.

[0013] Furthermore, in step S2, the temperature of the third heat treatment is 150~200℃, and the time of the third heat treatment is 1~10h.

[0014] According to another aspect of the present invention, a solid-state battery is provided, comprising an electrolyte, a positive electrode, and a negative electrode, wherein the electrolyte is the sulfide solid electrolyte described above or prepared by the preparation method described above.

[0015] By applying the technical solution of this invention, the sulfide solid electrolyte of this application, through the aforementioned double coating layer, can improve the ionic conductivity, air stability, and electrochemical stability of the sulfide solid electrolyte. Specifically, the first coating layer (lithium iodide layer) of this application can form a stable chemical bond with the core of the sulfide electrolyte, making it less prone to detachment during battery cycling. The lithium iodide in the first coating layer can actively induce uniform deposition of lithium ions and inhibit the growth of lithium dendrites, thereby greatly improving the air stability of the sulfide solid electrolyte and improving the stability of the sulfide solid electrolyte at the electrode interface, thereby reducing the interface impedance. In addition, the first coating layer has the ability to actively regulate lithium ion migration during battery operation, thereby achieving a technological leap from "passive protection" to "active interface regulation." This not only enables the sulfide solid electrolyte to maintain good ionic conductivity but also maintains good electrochemical stability at the lithium metal anode interface, forming a stable solid electrolyte interface layer during battery cycling, thereby improving the cycle stability of the battery. The iodine in the second coating layer (iodine layer) is hydrophobic, which not only fills the microscopic defects on the surface of the first coating layer but also forms a dense physical barrier layer, thereby further improving the air stability of the sulfide solid electrolyte. In summary, the sulfide solid electrolyte of this application exhibits high ionic conductivity, good air stability and electrochemical stability, and the coating layer is not easily detached, thus improving the electrochemical performance and cycle performance of the battery and extending its cycle life. Detailed Implementation

[0016] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0017] As analyzed in the background section of this application, existing sulfide solid electrolytes suffer from poor air stability and electrochemical stability. To address these issues, this application provides a sulfide solid electrolyte, its preparation method, and a solid-state battery.

[0018] In a typical embodiment of this application, a sulfide solid electrolyte is provided, which includes a sulfide electrolyte core and a first coating layer and a second coating layer sequentially coating the outer surface of the sulfide electrolyte core from the inside out; the first coating layer includes lithium iodide; and the second coating layer includes elemental iodine.

[0019] The sulfide solid electrolyte of this application, through the aforementioned double coating layer, can improve the ionic conductivity, air stability, and electrochemical stability of the sulfide solid electrolyte. Specifically, the first coating layer (lithium iodide layer) of this application can form a stable chemical bond with the core of the sulfide electrolyte, making it less prone to detachment during battery cycling. The lithium iodide in the first coating layer can actively induce uniform deposition of lithium ions and inhibit the growth of lithium dendrites, thereby greatly improving the air stability of the sulfide solid electrolyte and improving the stability of the sulfide solid electrolyte at the electrode interface, thus reducing the interface impedance. In addition, the first coating layer has the ability to actively regulate lithium ion migration during battery operation, thereby achieving a technological leap from "passive protection" to "active interface regulation." This not only enables the sulfide solid electrolyte to maintain good ionic conductivity but also maintains good electrochemical stability at the lithium metal anode interface, forming a stable solid electrolyte interface layer during battery cycling, thereby improving the cycle stability of the battery. The iodine in the second coating layer (iodine layer) is hydrophobic, which not only fills the microscopic defects on the surface of the first coating layer but also forms a dense physical barrier layer, thereby further improving the air stability of the sulfide solid electrolyte. In summary, the sulfide solid electrolyte of this application exhibits high ionic conductivity, good air stability and electrochemical stability, and the coating layer is not easily detached, thus improving the electrochemical performance and cycle performance of the battery and extending its cycle life.

[0020] In one embodiment of this application, the chemical formula of the sulfide electrolyte core is (100-xy)Li2S·xP2S5·yM m N n , 0≤x<100, 0≤y<100, 0≤x+y<100, 0≤m<4, 0≤n<6, M is selected from any one or more of Li, Ge, Si, Sn and Sb, and N is selected from any one or more of Se, O, Cl, Br and I.

[0021] The preferred method uses a sulfide electrolyte core with the aforementioned chemical formula, and controlling the types of M and N elements within the above range. This helps the sulfide solid electrolyte expand the lithium-ion transport channels, reduce the activation energy of lithium-ion migration, and also helps to adjust the rigidity of the sulfide electrolyte core lattice and the strength of chemical bonds, ensuring a tight bond between it and the first coating layer through chemical bonds. The chemical formula of the sulfide electrolyte core is its chemical formula before reaction with the iodine source. The sulfide electrolyte core is selected from Li6PS5Cl, Li... 10 GeP2S 12 Li7P2S8I, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Li7P2S8I0.5 Br 0.5 Li 10 SnP2S 12 Li3PSbS5Cl and Li6PS 4.5 Se 0.3 O 0.2 Any one or more of Cl. Preferably, when M is Li, N is any one or more of Cl, Br, and I. More preferably, the sulfide electrolyte core is selected from Li6PS5Cl, Li 10 GeP2S 12 And any one or more of Li7P2S8I. Furthermore, x and y represent mole percentages.

[0022] In one embodiment of this application, the D50 particle size of the sulfide electrolyte core is 2~10μm; and / or, the mass percentage of the first coating layer in the sulfide solid electrolyte is 0.1~6%; and / or, the mass percentage of the second coating layer in the sulfide solid electrolyte is 0.1~6%.

[0023] The preferred D50 particle size of the sulfide electrolyte core is within the aforementioned range. This not only helps to better coat the outer surface of the coating layer but also helps to maintain a high packing density, better match the active material to form a continuous lithium-ion transport network, increase the solid-solid contact area, and reduce interfacial impedance. The preferred mass percentage of the first coating layer in the sulfide solid electrolyte is within the aforementioned range. This not only helps to better form a stable chemical bond with the sulfide electrolyte core, making it less prone to detachment during battery cycling, but also helps to improve the air stability of the sulfide solid electrolyte and the stability of the sulfide solid electrolyte to the electrode interface, thereby reducing interfacial impedance. The preferred mass percentage of the second coating layer in the sulfide solid electrolyte is within the aforementioned range. This helps to improve the density of the second coating layer, thereby improving the barrier effect and further improving the air stability of the sulfide solid electrolyte. Furthermore, the mass percentage of the first coating layer in the sulfide solid electrolyte can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or 6%, etc. The mass percentage of the second coating layer in a sulfide solid electrolyte can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or 6%, etc.

[0024] In one embodiment of this application, the mass ratio of the first coating layer to the second coating layer is (0.2~5):1.

[0025] Preferably, the mass ratio of the first coating layer to the second coating layer is within the aforementioned range, which helps to enhance their synergistic effect, thereby further improving the ionic conductivity, air stability, and chemical stability of the sulfide solid electrolyte, and thus improving the electrochemical performance and cycle stability of the battery. Furthermore, the mass ratio of the first coating layer to the second coating layer can be 0.2:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, or 5:1, etc.

[0026] In another typical embodiment of this application, a method for preparing the above-mentioned sulfide solid electrolyte is provided. The method includes: step S1, mixing raw materials including a sulfide electrolyte core and an iodine source and performing a first heat treatment, whereby the iodine source forms iodine vapor and deposits on the outer surface of the sulfide electrolyte core, and then performing a second heat treatment to generate lithium iodide on the outer surface of the sulfide electrolyte core, forming a first coating layer, and obtaining an intermediate product; step S2, performing a third heat treatment on the intermediate product to deposit elemental iodine on the outer surface of the intermediate product, forming a second coating layer, and obtaining a sulfide solid electrolyte; wherein the temperature of the second heat treatment is higher than the temperature of the first heat treatment.

[0027] In step S1 of this application, the iodine source is first sublimated and deposited on the outer surface of the sulfide electrolyte core through a first heat treatment. Then, a second heat treatment is performed at a higher temperature to cause the deposited iodine source and the sulfide electrolyte core to react in situ to generate lithium iodide. The resulting first coating layer is chemically bonded to the sulfide electrolyte core, making it less prone to detachment during long-term battery cycling and significantly improving structural stability. The lithium iodide in the first coating layer can actively induce uniform lithium ion deposition and inhibit lithium dendrite growth, thereby greatly improving the air stability of the sulfide solid electrolyte and the stability of the sulfide solid electrolyte at the electrode interface, thus reducing interface impedance. The first coating layer has the ability to actively regulate lithium ion migration during battery operation, thus achieving a technological leap from "passive protection" to "active interface regulation." It not only maintains good ion conductivity of the sulfide solid electrolyte but also maintains good electrochemical stability at the lithium metal anode interface, forming a stable solid electrolyte interface layer during battery cycling, thereby improving the cycle stability of the battery. In step S2 of this application, a third heat treatment is used to deposit the iodine source that did not participate in the in-situ reaction in step S1 onto the outer surface of the first coating layer, forming a second coating layer. The second coating layer is hydrophobic, which not only fills the microscopic defects on the surface of the first coating layer but also forms a dense physical barrier layer, thereby further improving the air stability of the sulfide solid electrolyte. In summary, the preparation method of this application is simple, energy-efficient, and has a high yield, enabling large-scale production.

[0028] In one embodiment of this application, in step S1, the mass ratio of the sulfide electrolyte core to the iodine source is 100:(0.5~10), and the iodine source is elemental iodine material.

[0029] The preferred mass ratio of the sulfide electrolyte core to the iodine source within the aforementioned range not only facilitates the reaction between the sulfide electrolyte core and the iodine source to generate lithium iodide and form the first coating layer, but also facilitates the continued deposition of elemental iodine on the surface of the first coating layer to form a second coating layer. This improves the density and stability of both the first and second coating layers, thereby enhancing the air stability and electrochemical stability of the sulfide solid electrolyte. Preferably, the iodine source is elemental iodine, which helps provide pure raw materials for obtaining stable first and second coating layers and reduces the introduction of impurities. Furthermore, the preferred mass ratio of the sulfide electrolyte core to the iodine source is 100:0.5, 100:1, 100:3, 100:5, 100:7, 100:9, 100:10, etc.

[0030] In one embodiment of this application, in step S1, the mixing time is 0.5~3h, the mixing temperature is 20~30℃, and the mixing atmosphere is argon and / or nitrogen; the mixing method is selected from any one or more of stirring mixing, shearing mixing, ball milling mixing, twin-screw extrusion mixing, and grinding mixing.

[0031] The optimal mixing temperature, time, atmosphere, and mixing method are within the above ranges, which helps the particle surface of the sulfide electrolyte core to fully contact the iodine vapor, thereby allowing the iodine source to be uniformly deposited on the outer surface of the sulfide electrolyte core. This, in turn, facilitates the subsequent reaction of iodine vapor with the sulfide electrolyte core to generate lithium iodide, forming the first coating layer.

[0032] In one embodiment of this application, in step S1, the temperature of the first heat treatment is 40~100℃ and the time of the first heat treatment is 1~24h; the temperature of the second heat treatment is 150~300℃ and the time of the second heat treatment is 1~8h.

[0033] The preferred temperature and time for the first heat treatment are within the aforementioned ranges, which facilitates the complete sublimation of the iodine source, thereby ensuring uniform deposition on the outer surface of the sulfide electrolyte core. Furthermore, the temperature for the first heat treatment can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, or 100°C, etc. The duration of the first heat treatment can be 1 hour, 3 hours, 5 hours, 7 hours, 10 hours, 12 hours, 14 hours, 16 hours, 20 hours, or 24 hours, etc.

[0034] Preferably, the temperature and time of the second heat treatment are within the above-mentioned range, which helps to promote the in-situ chemical reaction between iodine vapor and the sulfide electrolyte core, thereby forming a dense and firmly bonded lithium iodide layer. Furthermore, the temperature of the second heat treatment can be 150°C, 180°C, 200°C, 220°C, 250°C, 270°C, or 300°C, etc. The time of the second heat treatment can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, or 8 hours, etc.

[0035] In one embodiment of this application, in step S2, the temperature of the third heat treatment is 150~200℃, and the time of the third heat treatment is 1~10h.

[0036] Preferably, the temperature and time of the third heat treatment are within the above-mentioned range, which helps iodine vapor to continue depositing on the outer surface of the first coating layer to form a second coating layer, thereby further improving the air stability of the sulfide solid electrolyte. Furthermore, the temperature of the third heat treatment can be 150°C, 160°C, 170°C, 180°C, 190°C, or 200°C, etc. The time of the third heat treatment can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours, etc.

[0037] The preferred temperature for the second heat treatment is 50-200°C higher than that for the first heat treatment, and the temperature for the third heat treatment is 50-100°C lower than that for the second heat treatment. This helps to create a gradient temperature control for iodine during sublimation, in-situ reaction, and secondary deposition. This ensures that the first coating layer is densely formed while the remaining iodine vapor condenses on the outer layer with a suitable degree of supersaturation. This results in a double-layer protective structure with tight chemical bonding and complete physical barrier, simultaneously improving ionic conductivity, air stability, and lithium cycle stability.

[0038] The above-mentioned heat treatment processes in this application can all be completed continuously in the same sealed container without changing equipment or introducing additional reagents (lithium element comes from the sulfide solid electrolyte itself), making it suitable for mass production.

[0039] In another typical embodiment of this application, a solid-state battery is provided, comprising an electrolyte, a positive electrode, and a negative electrode, wherein the electrolyte is the sulfide solid electrolyte described above or prepared by the preparation method described above.

[0040] The sulfide solid electrolyte of this application has high ionic conductivity, good air stability and electrochemical stability, and the coating layer is not easy to fall off, which makes the solid battery have good electrochemical performance, cycle performance and long cycle life.

[0041] The beneficial effects of this application will be further illustrated below with reference to the embodiments.

[0042] Example 1

[0043] Raw materials: The sulfide electrolyte core is Li6PS5Cl, the D50 particle size of the sulfide electrolyte core is 5μm, the iodine source is elemental iodine, and the mass ratio of the sulfide electrolyte core to the iodine source is 100:5.

[0044] Preparation of sulfide solid electrolytes:

[0045] Step S1: The sulfide electrolyte core and elemental iodine are ground and mixed in a mortar under an argon atmosphere for 0.5 h. After uniform mixing, the mixture is placed in a sealed container for a first heat treatment at a temperature of 80 °C for 10 h. During this process, elemental iodine sublimates into iodine vapor, filling the entire sealed container and uniformly depositing on the outer surface of the sulfide electrolyte core. A second heat treatment is then performed at a temperature of 150 °C for 2 h, generating lithium iodide on the outer surface of the sulfide electrolyte core, forming the first coating layer, and yielding the intermediate product.

[0046] Step S2: The intermediate product is subjected to a third heat treatment at a temperature of 180°C for 4 hours to deposit elemental iodine on the outer surface of the intermediate product, forming a second coating layer to obtain a sulfide solid electrolyte.

[0047] The sulfide solid electrolyte consists of a sulfide electrolyte core and a first coating layer and a second coating layer that are sequentially coated on the outer surface of the sulfide electrolyte core from the inside out. The first coating layer accounts for 3% of the mass, and the second coating layer accounts for 2% of the mass.

[0048] Example 2

[0049] The difference from Example 1 is that the raw material: the sulfide electrolyte core is Li 10 GeP2S 12 The D50 particle size of the sulfide electrolyte core is 3 μm, the iodine source is elemental iodine, and the mass ratio of the sulfide electrolyte core to the iodine source is 100:0.5.

[0050] Preparation of sulfide solid electrolytes:

[0051] Step S1: The sulfide electrolyte core and elemental iodine are stirred and mixed under an argon atmosphere for 1 hour. After uniform mixing, the mixture is placed in a sealed container for a first heat treatment at a temperature of 40°C for 1 hour. During this process, elemental iodine sublimates into iodine vapor, filling the entire sealed container and uniformly depositing on the outer surface of the sulfide electrolyte core. A second heat treatment is then performed at a temperature of 200°C for 4 hours, resulting in the formation of lithium iodide on the outer surface of the sulfide electrolyte core, forming the first coating layer and yielding the intermediate product.

[0052] Step S2: The intermediate product is subjected to a third heat treatment at a temperature of 160°C for 3 hours to deposit elemental iodine on the outer surface of the intermediate product, forming a second coating layer to obtain a sulfide solid electrolyte.

[0053] In the sulfide solid electrolyte, the first coating layer accounts for 0.3% of the mass and the second coating layer accounts for 0.2% of the mass.

[0054] Example 3

[0055] The difference from Example 1 is that the raw materials are: the sulfide electrolyte core is Li7P2S8I, the D50 particle size of the sulfide electrolyte core is 8μm, the iodine source is elemental iodine, and the mass ratio of the sulfide electrolyte core to the iodine source is 100:10.

[0056] Preparation of sulfide solid electrolytes:

[0057] Step S1: The sulfide electrolyte core and elemental iodine are ball-milled and mixed under an argon atmosphere for 0.5 h. After uniform mixing, the mixture is placed in a sealed container for a first heat treatment at 60 °C for 18 h. During this process, elemental iodine sublimates into iodine vapor, filling the entire sealed container and uniformly depositing on the outer surface of the sulfide electrolyte core. A second heat treatment is then performed at 250 °C for 5 h, generating lithium iodide on the outer surface of the sulfide electrolyte core, forming the first coating layer, and yielding the intermediate product.

[0058] Step S2: The intermediate product is subjected to a third heat treatment at a temperature of 200°C for 6 hours to deposit iodine on the outer surface of the intermediate product, forming a second coating layer and obtaining a sulfide solid electrolyte.

[0059] In the sulfide solid electrolyte, the first coating layer accounts for 5.2% of the mass, the second coating layer accounts for 4.8% of the mass, and the mass ratio of the first coating layer to the second coating layer is 1.08:1.

[0060] Example 4

[0061] The difference from Example 1 is that the raw material: the sulfide electrolyte core is Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 The D50 particle size of the sulfide electrolyte core is 4 μm, the iodine source is elemental iodine, and the mass ratio of the sulfide electrolyte core to the iodine source is 100:3.

[0062] Preparation of sulfide solid electrolytes:

[0063] Step S1: The sulfide electrolyte core and elemental iodine are sheared and mixed under an argon atmosphere for 3 hours. After uniform mixing, the mixture is placed in a sealed container for a first heat treatment at 50°C for 24 hours. During this process, elemental iodine sublimates into iodine vapor, filling the entire sealed container and uniformly depositing on the outer surface of the sulfide electrolyte core. A second heat treatment is then performed at 180°C for 1 hour, generating lithium iodide on the outer surface of the sulfide electrolyte core, forming the first coating layer, and yielding the intermediate product.

[0064] Step S2: The intermediate product is subjected to a third heat treatment at a temperature of 150°C for 2 hours to deposit iodine on the outer surface of the intermediate product, forming a second coating layer and obtaining a sulfide solid electrolyte.

[0065] In the sulfide solid electrolyte, the mass percentage of the first coating layer is 1.5%, the mass percentage of the second coating layer is 1.5%, and the mass ratio of the first coating layer to the second coating layer is 1:1.

[0066] Example 5

[0067] The difference from Example 1 is that the raw material: the sulfide electrolyte core is Li7P2S8I. 0.5 Br 0.5 The D50 particle size of the sulfide electrolyte core is 6 μm, the iodine source is elemental iodine, and the mass ratio of the sulfide electrolyte core to the iodine source is 100:1.

[0068] Preparation of sulfide solid electrolytes:

[0069] Step S1: The sulfide electrolyte core and elemental iodine are ground and mixed in a mortar under an argon atmosphere for 40 minutes. After uniform mixing, the mixture is placed in a sealed container for a first heat treatment at a temperature of 70°C for 5 hours. During this process, elemental iodine sublimates into iodine vapor, filling the entire sealed container and uniformly depositing on the outer surface of the sulfide electrolyte core. A second heat treatment is then performed at a temperature of 300°C for 3 hours, resulting in the formation of lithium iodide on the outer surface of the sulfide electrolyte core, forming the first coating layer and yielding the intermediate product.

[0070] Step S2: The intermediate product is subjected to a third heat treatment at a temperature of 200°C for 5 hours to deposit iodine on the outer surface of the intermediate product, forming a second coating layer and obtaining a sulfide solid electrolyte.

[0071] In the sulfide solid electrolyte, the mass percentage of the first coating layer is 0.6%, the mass percentage of the second coating layer is 0.4%, and the mass ratio of the first coating layer to the second coating layer is 1.5:1.

[0072] Example 6

[0073] The difference from Example 1 is that the raw material: the sulfide electrolyte core is Li 10 SnP2S 12 The D50 particle size of the sulfide electrolyte core is 7 μm, the iodine source is elemental iodine, and the mass ratio of the sulfide electrolyte core to the iodine source is 100:7.

[0074] Preparation of sulfide solid electrolytes:

[0075] Step S1: The sulfide electrolyte core and elemental iodine are ball-milled and mixed under an argon atmosphere for 3 hours. After uniform mixing, the mixture is placed in a sealed container for a first heat treatment at 80°C for 10 hours. During this process, elemental iodine sublimates into iodine vapor, filling the entire sealed container and uniformly depositing on the outer surface of the sulfide electrolyte core. A second heat treatment is then performed at 150°C for 8 hours, generating lithium iodide on the outer surface of the sulfide electrolyte core, forming the first coating layer, and yielding the intermediate product.

[0076] Step S2: The intermediate product is subjected to a third heat treatment at a temperature of 150°C for 5 hours to deposit elemental iodine on the outer surface of the intermediate product, forming a second coating layer to obtain a sulfide solid electrolyte.

[0077] In the sulfide solid electrolyte, the first coating layer accounts for 3.5% of the mass, and the second coating layer accounts for 3.5% of the mass.

[0078] Example 7

[0079] The difference from Example 1 is that the raw materials are: the sulfide electrolyte core is Li3PSbS5Cl, the D50 particle size of the sulfide electrolyte core is 5μm, the iodine source is elemental iodine, and the mass ratio of the sulfide electrolyte core to the iodine source is 100:5.

[0080] Preparation of sulfide solid electrolytes:

[0081] Step S1: The sulfide electrolyte core and elemental iodine are ball-milled and mixed under an argon atmosphere for 3 hours. After uniform mixing, the mixture is placed in a sealed container for a first heat treatment at 80°C for 10 hours. A second heat treatment is then performed at 280°C for 2 hours. Lithium iodide is generated on the outer surface of the sulfide electrolyte core, forming the first coating layer, and an intermediate product is obtained.

[0082] Step S2: The intermediate product is subjected to a third heat treatment at a temperature of 200°C for 3 hours to deposit elemental iodine on the outer surface of the intermediate product, forming a second coating layer to obtain a sulfide solid electrolyte.

[0083] In the sulfide solid electrolyte, the first coating layer accounts for 2.5% of the mass, and the second coating layer accounts for 2.5% of the mass.

[0084] Example 8

[0085] The difference from Example 1 is that the sulfide electrolyte core is Li6PS. 4.5 Se 0.3 O 0.2 Cl, the D50 particle size of the sulfide electrolyte core is 5 μm, the iodine source is elemental iodine, and the mass ratio of the sulfide electrolyte core to the iodine source is 100:5.

[0086] Preparation of sulfide solid electrolytes:

[0087] Step S1: The sulfide electrolyte core and elemental iodine are ball-milled and mixed under an argon atmosphere for 3 hours. After uniform mixing, the mixture is placed in a sealed container for a first heat treatment at 80°C for 10 hours. During this process, elemental iodine sublimates into iodine vapor, filling the entire sealed container and uniformly depositing on the outer surface of the sulfide electrolyte core. A second heat treatment is then performed at 250°C for 2 hours, generating lithium iodide on the outer surface of the sulfide electrolyte core, forming the first coating layer, and yielding the intermediate product.

[0088] Step S2: The intermediate product is subjected to a third heat treatment at a temperature of 190°C for 4 hours to deposit elemental iodine on the outer surface of the intermediate product, forming a second coating layer to obtain a sulfide solid electrolyte.

[0089] In the sulfide solid electrolyte, the first coating layer accounts for 2.5% of the mass, and the second coating layer accounts for 2.5% of the mass.

[0090] Example 9

[0091] The difference from Example 1 is that the mass ratio of the sulfide electrolyte core to the iodine source is 100:20, and a sulfide solid electrolyte is finally obtained. The mass ratio of the first coating layer is 9.5%, and the mass ratio of the second coating layer is 10.5%.

[0092] Example 10

[0093] The difference from Example 1 is that the mass ratio of the sulfide electrolyte core to the iodine source is 100:0.1, and a sulfide solid electrolyte is finally obtained. The mass ratio of the first coating layer is 0.06%, and the mass ratio of the second coating layer is 0.04%.

[0094] Example 11

[0095] The difference from Example 1 is that the temperature of the first heat treatment is 60°C and the time of the first heat treatment is 18h, the temperature of the second heat treatment is 150°C and the time of the second heat treatment is 1h, and finally a sulfide solid electrolyte is obtained.

[0096] Example 12

[0097] The difference from Example 1 is that the temperature of the first heat treatment is 120°C and the time of the first heat treatment is 0.5h, the temperature of the second heat treatment is 350°C and the time of the second heat treatment is 0.5h, and finally a sulfide solid electrolyte is obtained.

[0098] Example 13

[0099] The difference from Example 1 is that the temperature of the first heat treatment is 35°C and the time of the first heat treatment is 30h, the temperature of the second heat treatment is 120°C and the time of the second heat treatment is 10h, and finally a sulfide solid electrolyte is obtained.

[0100] Example 14

[0101] The difference from Example 1 is that the temperature of the third heat treatment is 150°C and the time of the third heat treatment is 10 hours, and finally a sulfide solid electrolyte is obtained.

[0102] Example 15

[0103] The difference from Example 1 is that the temperature of the third heat treatment is 300°C and the time of the third heat treatment is 0.5h, and finally a sulfide solid electrolyte is obtained.

[0104] Example 16

[0105] The difference from Example 1 is that the mass ratio of the sulfide electrolyte core to the iodine source is 100:5, and the mass ratio of the first coating layer to the second coating layer is 5:1, ultimately yielding a sulfide solid electrolyte.

[0106] Example 17

[0107] The difference from Example 1 is that the mass ratio of the sulfide electrolyte core to the iodine source is 100:5, and the mass ratio of the first coating layer to the second coating layer is 10:1, ultimately yielding a sulfide solid electrolyte.

[0108] Example 18

[0109] The difference from Example 1 is that the temperature of the first heat treatment is 60°C, the temperature of the second heat treatment is 250°C, and the temperature of the third heat treatment is 180°C. The temperature of the second heat treatment is 190°C higher than that of the first heat treatment, and the temperature of the third heat treatment is 70°C lower than that of the second heat treatment, ultimately yielding a sulfide solid electrolyte.

[0110] Comparative Example 1

[0111] The difference from Example 1 is that no iodine source is added, and a sulfide solid electrolyte is finally obtained.

[0112] Comparative Example 2

[0113] The difference from Example 2 is that no iodine source is added, and a sulfide solid electrolyte is finally obtained.

[0114] Comparative Example 3

[0115] The difference from Example 3 is that no iodine source is added, and a sulfide solid electrolyte is finally obtained.

[0116] Comparative Example 4

[0117] The difference from Example 4 is that no iodine source is added, and a sulfide solid electrolyte is finally obtained.

[0118] Comparative Example 5

[0119] The difference from Example 5 is that no iodine source is added, and a sulfide solid electrolyte is finally obtained.

[0120] Comparative Example 6

[0121] The difference from Example 6 is that no iodine source is added, and a sulfide solid electrolyte is finally obtained.

[0122] Comparative Example 7

[0123] The difference from Example 7 is that no iodine source is added, and a sulfide solid electrolyte is finally obtained.

[0124] Comparative Example 8

[0125] The difference from Example 8 is that no iodine source is added, and a sulfide solid electrolyte is finally obtained.

[0126] Comparative Example 9

[0127] The difference from Example 1 is that the iodine element and the sulfide electrolyte core are only physically ground and mixed without any heat treatment, and finally a sulfide solid electrolyte is obtained.

[0128] Comparative Example 10

[0129] The difference from Example 1 is that the sulfide solid electrolyte is only coated with the first coating layer and has no second coating layer.

[0130] Comparative Example 11

[0131] The difference from Example 1 is that the sulfide solid electrolyte is only coated with a second coating layer (iodine elemental layer) and has no first coating layer.

[0132] Test method:

[0133] Ionic conductivity: Weigh 300 mg of sulfide solid electrolyte, cold-press it into a sheet, and use stainless steel as the blocking electrode for AC impedance testing. Take the value of Z′ at the intersection of the straight line and the Z′ axis as the total impedance R of the solid electrolyte, and then calculate the ionic conductivity. The formula for calculating ionic conductivity is: σ = L / (R × S); where L is the sample thickness, R is the total impedance, and S is the effective contact area between the sample and the electrode.

[0134] Electrochemical stability of lithium metal: A lithium-lithium symmetric battery was assembled using lithium metal sheets as electrodes and a sulfide solid electrolyte as a solid electrolyte, achieving an electrochemical stability of 0.2 mA / cm². 2 The current density is 0.5 mAh / cm³. 2 The deposition capacity was tested by cycling, and the number of cycles was recorded. The number of cycles refers to the deposition-dissolution process of lithium metal on the positive and negative electrode surfaces. The comparison of the number of cycles helps to verify the electrochemical stability of the solid electrolyte.

[0135] Air stability test: Weigh 1g of sulfide solid electrolyte powder and place it in a constant temperature and humidity chamber with a relative humidity of 50% and a temperature of 25℃ for 24 hours. Then, perform AC impedance test according to the method in the initial ionic conductivity test and calculate the ionic conductivity after 24 hours of exposure.

[0136] The test results are shown in Table 1.

[0137] Table 1

[0138]

[0139] As can be seen from the above, the embodiments of this application involve sublimating and depositing elemental iodine onto the outer surface of the sulfide electrolyte core, followed by a second heat treatment. This allows the elemental iodine to react in situ with the lithium element in the sulfide electrolyte core, forming a lithium iodide coating layer in situ on the outer surface of the sulfide electrolyte core. The coating layer obtained by this method has strong adhesion and is not easily peeled off. Furthermore, lithium iodide itself has a 10 -5 With an ionic conductivity on the order of S / cm, it can partially fill defects and voids on the surface of the sulfide electrolyte core, forming additional lithium-ion channels, thereby further improving the room-temperature ionic conductivity of the coated electrolyte.

[0140] The embodiments of this application all exhibit excellent air stability, with ionic conductivity retention exceeding 80% after 24 hours. The lithium iodide layer exhibits higher density and forms chemical bonds with the sulfide electrolyte core, reducing the channels for water molecule permeation along the interface; the residual iodine retains its hydrophobic properties. Furthermore, the cycle stability of the battery is significantly improved because lithium iodide has thermodynamic stability to lithium metal and can participate in the formation of a LiI-rich SEI layer during cycling, thereby effectively suppressing lithium dendrites and interfacial side reactions.

[0141] The sulfide solid electrolyte of Comparative Example 9 only physically coats iodine, resulting in no chemical bond between iodine and the core. It is attached only by van der Waals forces, and the iodine layer is very easy to fall off during battery cycling and air exposure. At the same time, iodine cannot react in situ with lithium in the core to form lithium iodide. It lacks a chemical protective layer and interface regulation function. Therefore, its air stability and cycling performance are significantly worse than those of the Example.

[0142] In Comparative Example 10, the sulfide solid electrolyte only had a first coating layer and lacked a second coating layer. This resulted in a lack of physical barrier protection from the hydrophobic iodine layer, allowing water molecules to more easily penetrate the lithium iodide layer and the core surface, thus reducing the air stability of the sulfide solid electrolyte. Furthermore, the microscopic defects on the surface of the first coating layer could not be filled by iodine, reducing interfacial density and affecting the protective effect on lithium metal.

[0143] In Comparative Example 11, the sulfide solid electrolyte is only coated with a second coating layer (iodine layer) and lacks a first coating layer, resulting in the absence of a lithium iodide layer. This prevents the formation of a chemically bonded protective layer and the ability to regulate the interface of lithium metal. The physical barrier of iodine alone is insufficient to suppress interfacial side reactions and lithium dendrite growth, resulting in a significantly lower cycle stability than in the examples. Air stability is also insufficient due to the lack of chemical protection.

[0144] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0145] The sulfide solid electrolyte of this application, through the aforementioned double coating layer, can improve the ionic conductivity, air stability, and electrochemical stability of the sulfide solid electrolyte. Specifically, the first coating layer (lithium iodide layer) of this application can form a stable chemical bond with the core of the sulfide electrolyte, making it less prone to detachment during battery cycling. The lithium iodide in the first coating layer can actively induce uniform deposition of lithium ions and inhibit the growth of lithium dendrites, thereby greatly improving the air stability of the sulfide solid electrolyte and improving the stability of the sulfide solid electrolyte at the electrode interface, thus reducing the interface impedance. In addition, the first coating layer has the ability to actively regulate lithium ion migration during battery operation, thereby achieving a technological leap from "passive protection" to "active interface regulation." This not only enables the sulfide solid electrolyte to maintain good ionic conductivity but also maintains good electrochemical stability at the lithium metal anode interface, forming a stable solid electrolyte interface layer during battery cycling, thereby improving the cycle stability of the battery. The iodine in the second coating layer (iodine layer) is hydrophobic, which not only fills the microscopic defects on the surface of the first coating layer but also forms a dense physical barrier layer, thereby further improving the air stability of the sulfide solid electrolyte. In summary, the sulfide solid electrolyte of this application exhibits high ionic conductivity, good air stability and electrochemical stability, and the coating layer is not easily detached, thus improving the electrochemical performance and cycle performance of the battery and extending its cycle life.

[0146] The above are merely embodiments of the present invention and are not intended to limit the invention. Those skilled in the art will recognize that the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A sulfide solid electrolyte, characterized in that, The sulfide solid electrolyte includes a sulfide electrolyte core and a first coating layer and a second coating layer that are sequentially coated on the outer surface of the sulfide electrolyte core from the inside out. The first coating layer includes lithium iodide; The second coating layer includes elemental iodine.

2. The sulfide solid electrolyte according to claim 1, characterized in that, The chemical formula of the sulfide electrolyte core is (100-xy)Li₂S·xP₂S₅·yM. m N n , 0≤x<100, 0≤y<100, 0≤x+y<100, 0≤m<4, 0≤n<6, M is selected from any one or more of Li, Ge, Si, Sn and Sb, and N is selected from any one or more of Se, S, O, Cl, Br and I.

3. The sulfide solid electrolyte according to claim 1 or 2, characterized in that, The D50 particle size of the sulfide electrolyte core is 2~10μm; and / or, the mass percentage of the first coating layer in the sulfide solid electrolyte is 0.1~6%; and / or, the mass percentage of the second coating layer in the sulfide solid electrolyte is 0.1~6%.

4. The sulfide solid electrolyte according to claim 3, characterized in that, The mass ratio of the first coating layer to the second coating layer is (0.2~5):

1.

5. A method for preparing a sulfide solid electrolyte according to any one of claims 1 to 4, characterized in that, The preparation method includes: Step S1: After mixing the raw materials including the sulfide electrolyte core and the iodine source, a first heat treatment is performed. The iodine source forms iodine vapor and is deposited on the outer surface of the sulfide electrolyte core. A second heat treatment is then performed to generate lithium iodide on the outer surface of the sulfide electrolyte core, forming a first coating layer, and an intermediate product is obtained. Step S2: The intermediate product is subjected to a third heat treatment to deposit elemental iodine on the outer surface of the intermediate product to form a second coating layer, thereby obtaining the sulfide solid electrolyte. The temperature of the second heat treatment is higher than the temperature of the first heat treatment.

6. The preparation method according to claim 5, characterized in that, In step S1, the mass ratio of the sulfide electrolyte core to the iodine source is 100:(0.5~10), and the iodine source is an elemental iodine material.

7. The preparation method according to claim 5, characterized in that, In step S1, the mixing time is 0.5-3 hours, the mixing temperature is 20-30°C, and the mixing atmosphere is argon and / or nitrogen. The mixing method is selected from any one or more of stirring mixing, shear mixing, ball milling mixing, twin-screw extrusion mixing, and grinding mixing.

8. The preparation method according to any one of claims 5 to 7, characterized in that, In step S1, the temperature of the first heat treatment is 40~100℃, and the time of the first heat treatment is 1~24h. The temperature of the second heat treatment is 150~300℃, and the time of the second heat treatment is 1~8h.

9. The preparation method according to any one of claims 5 to 7, characterized in that, In step S2, the temperature of the third heat treatment is 150~200℃, and the time of the third heat treatment is 1~10h.

10. A solid-state battery, comprising an electrolyte, a positive electrode, and a negative electrode, characterized in that, The electrolyte is a sulfide solid electrolyte as described in any one of claims 1 to 4 or is prepared by the preparation method as described in any one of claims 5 to 9.

Citation Information

Patent Citations

  • High-air-stability inorganic sulfide solid electrolyte and preparation method and application thereof

    CN110085908A